Implementation of Problem-Based Learning Model to Improve Mathematical Problem-Solving Skills of Grade XI-2 Students of SMAN 19 Pekanbaru - Yuni Hariati Siahaan; Syarifah Nur Siregar; Atma Murni (Jurnal Didactical Mathematics, 2026)
This study aimed to improve students’ mathematical problem-solving ability through the implementation of the Problem-Based Learning (PBL) model in mathematics instruction. The study employed a collaborative Classroom Action Research (CAR) design conducted in two cycles involving planning, implementation, observation, and reflection stages. The participants consisted of 41 students of Grade XI-2 at SMAN 19 Pekanbaru during the odd semester of the 2025/2026 academic year. Data were collected through classroom observation and mathematical problem-solving ability tests based on four indicators adapted from Polya’s problem-solving framework, namely understanding the problem, planning the solution, carrying out the solution, and checking back. Data analysis was conducted quantitatively and qualitatively to examine the progression of students’ mathematical problem-solving performance and classroom learning activities across cycles. The findings revealed that the implementation of PBL contributed positively to improving both the learning process and students’ mathematical problem-solving ability. The average class score increased from 33.90 in the initial test to 67.80 in Cycle I and further improved to 73.41 in Cycle II. Improvement was also observed across all problem-solving indicators, particularly in the planning and checking back indicators, indicating stronger strategic reasoning and reflective evaluation skills among students. In addition, students demonstrated increased participation, collaborative engagement, analytical discussion, and confidence in communicating mathematical ideas during learning activities. These findings suggest that Problem-Based Learning can create a more inquiry-oriented and cognitively engaging mathematics learning environment that supports the development of higher-order mathematical thinking and reflective problem-solving skills.